Finding the Great Western Trail - Mahoney, Sylvia Gann, 1939- (Book collections on Project MUSE., 2015)
"The Great Western Trail (GWT) is a nineteenth-century cattle trail that originated in northern Mexico, ran west parallel to the Chisholm Trail, traversed the United States for some two thousand miles, and terminated after crossing the Canadian border. Yet through time, misinformation, and the perpetuation of error, the historic path of this once-crucial cattle trail has been lost. Finding the Great Western Trail documents the first multi-community effort made to recover evidence and verify the route of the Great Western Trail. The GWT had long been celebrated in two neighboring communities: Vernon, Texas, and Altus, Oklahoma. Separated by the Red River, a natural border that cattle trail drovers forded with their herds, both Vernon and Altus maintained a living trail history with exhibits at local museums, annual trail-related events, ongoing narratives from local descendants of drovers, and historical monuments and structures. So when Western Trail Historical Society members in Altus challenged the Vernon Rotary Club to mark the trail across Texas every six miles, the effort soon spread along the trail in part through Rotary networks from Mexico, across nine US states, and into Saskatchewan, Canada. This book is the story of finding and marking the trail, and it stands as a record of each community's efforts to uncover their own GWT history. What began as local bravado transformed into a grass-roots project that, one hopes, will bring the previously obscured history of the Great Western Trail to light"--